The Analysis of Perceptions and Implementation of Pedagogical Content Knowledge of Teaching English to Young Learners by English Primary School Teachers in Klungkung - Yuanda Khristata Da Silva; I.G.A. Lokita Purnamika; Ida Ayu Made Istri Utami (Universitas PGRI Madiun, 2020)
This research aimed at analyzing the perceptions and the implementation of Pedagogical Content Knowledge (PCK) of teaching English to young learners by English Primary School Teachers in Klungkung. The research design was embedded mixed method design which interpreted dominantly qualitative. The research subjects were three different English Primary School Teachers in Klungkung. The result showed that there were gaps between teachers’ perceptions and implementation of pedagogical content knowledge. The final result of teachers’ perceptions categorized as high and qualified as strong, which is in interval 3.3335 ≤ M ≤ 4.0005. Meanwhile, the final result of teachers’ implementation categorized as very low and qualified as very weak, which is in interval 0.33 ≤ M ≤ 7.41. Some challenges were found as the causes of teachers’ very weak implementation of PCK. Besides, English teachers’ awareness to improve their practice quality regarding PCK of teaching English to young learners needs improving.